Market Orientation and Innovation Performance: Mediating Effects of Customer Engagement in SMEs - Ni Made Wahyuni; I Made Sara (Journal of Economics, Business, and Accountancy Ventura, 2020)
This study's objective is to develop an innovation performance model based on the role of market orientation and customer engagement. Market-oriented practices through customer engagement will enable companies to achieve innovation performance. This research was conducted on small and medium enterprises (SMEs) engaged in manu-facturing in Bali. A conceptual model was developed to determine the mediating role of customer engagement in the relationship between market orientation and innovation performance. The research design used was cross-sectional. Quantitative data were collected from 242 respondents by distributing questionnaires to managers and own-ers of manufacturing SMEs in Bali. The model was tested using Partial Least Square (PLS). The results of this study show that market orientation has a significant positive effect on innovation performance, market orientation has a positive effect on customer engagement, customer engagement has a positive effect on innovation performance, and customer engagement partially mediates the relationship between market orienta-tion and innovation performance. The results of this study are expected to be able to increase managers' insight and understanding of the mechanisms of how market ori-entation and customer engagement can contribute to innovation performance in ex-port-oriented SMEs.